2020
DOI: 10.1097/or9.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ perception of psychosocial issues of pediatric patients with osteosarcoma: an exploratory study

Abstract: Background: Survival of children treated for osteosarcoma across India has improved from just 44% in 2001 (Chennai only) to 88.6% in 2016. Advances in treatment (chemotherapy, limb salvage surgery, or limb amputation) impact patients’ ability to work, body image, functional abilities, and recreational activities. Despite this, only little attention has been given to the psychosocial issues of children with osteosarcoma or their caregivers. Aim: The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…32,33 While these overtly appeared physical, they further extended to psychosocial concerns such as low mood, feeling anxious or helplessness, and overall worry about the patient's well-being among caregivers 32,33 The impact on education and activities of the patients were explored with most parents and caregivers reporting concern regarding the child being unable to complete activities or milestones that their peers would be, falling behind and have difficulty cultivating new social relationships and maintaining existing ones. 32,33 Stigma was reported as a major concern, with parents and caregivers reporting that responses such as pity from others would cause the patients to lose self-confidence and it was difficult for them to address these issues with their friends to make play or activities more inclusive or suitable to the child's needs. 33 While fewer patients themselves reported distress, 33 parental perception of distress was greater.…”
Section: Patient Needs and Psychosocial Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 While these overtly appeared physical, they further extended to psychosocial concerns such as low mood, feeling anxious or helplessness, and overall worry about the patient's well-being among caregivers 32,33 The impact on education and activities of the patients were explored with most parents and caregivers reporting concern regarding the child being unable to complete activities or milestones that their peers would be, falling behind and have difficulty cultivating new social relationships and maintaining existing ones. 32,33 Stigma was reported as a major concern, with parents and caregivers reporting that responses such as pity from others would cause the patients to lose self-confidence and it was difficult for them to address these issues with their friends to make play or activities more inclusive or suitable to the child's needs. 33 While fewer patients themselves reported distress, 33 parental perception of distress was greater.…”
Section: Patient Needs and Psychosocial Concernsmentioning
confidence: 99%
“…33 While fewer patients themselves reported distress, 33 parental perception of distress was greater. 32 Across studies, the need for informational support presented either directly 33 or indirectly (as concern over uncertainty of prognosis) as well as a distinct apprehension regarding relapse and subsequently responding to questions related to mortality by the patient. 32…”
Section: Patient Needs and Psychosocial Concernsmentioning
confidence: 99%
“…Meanwhile, the use of chemotherapeutic drugs may put patients at increased risk of complications, such as vomiting, secondary malignancies, and heart failure (Zhang et al, 2018 ; Bhagat and Kleinerman, 2020 ). As a result, the parents of pediatric and adolescent patients with osteosarcoma usually bear a huge psychological burden, which may induce psychological diseases, such as anxiety, depression, and post-traumatic stress disorder (PTSD) (Yonemoto et al, 2012 ; Shunmugasundaram and Veeraiah, 2020 ). Therefore, for the parents of patients with osteosarcoma, who may also suffer from the abovementioned mental diseases, it is particularly important to find an intervention method to relieve their psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of psychosocial aspects on caregivers most often the parents cannot be stressed enough. Many caregivers experience to name a few, a multitude of complex emotions, have to assimilate information about the illness, be providers to their healthy children and provide round the clock care to the patient 2‐4 . A study by Kearney et al on Standard of Psychosocial care for parents of children with cancer high‐lighted multiple studies which reported that both parents were likely to exhibit significant distress which sometimes lasted up to 5 years post‐diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many caregivers experience to name a few, a multitude of complex emotions, have to assimilate information about the illness, be providers to their healthy children and provide round the clock care to the patient. 2 , 3 , 4 A study by Kearney et al on Standard of Psychosocial care for parents of children with cancer high‐lighted multiple studies which reported that both parents were likely to exhibit significant distress which sometimes lasted up to 5 years post‐diagnosis. The negative impact of parental distress resulted in poorer quality of life (QOL), emotional, and physical health factors, dysfunctional family functioning and greater marital distress.…”
Section: Introductionmentioning
confidence: 99%